THE IMPACT OF GLOBALIZATION AND MODERNIZATION PROCESSES ON FAMILY TRADITIONS - Sultonov Akmaljon Hasanovich (Modern American Journals, 2025)
This article examines the impact of globalization and modernization processes on family traditions in contemporary society. Globalization, characterized by the intensification of economic, cultural, and informational exchanges across borders, alongside modernization driven by technological advancement and social transformation, has significantly reshaped family structures, roles, and value systems. The study analyzes how traditional family norms—such as intergenerational relations, marriage practices, gender roles, and child-rearing patterns—are influenced by global cultural flows, urbanization, labor mobility, and digital communication. Particular attention is given to the tension between the preservation of cultural identity and the adaptation to modern lifestyles. Using a qualitative analytical approach based on sociological and cultural theory, the article highlights both the challenges and opportunities that globalization and modernization present for family traditions. The findings suggest that while certain traditional practices are weakened or transformed, new hybrid forms of family traditions emerge, reflecting a dynamic balance between continuity and change. The article contributes to a deeper understanding of how families navigate social change in an increasingly interconnected world.
Keywords: Globalization, modernization, family traditions, cultural transformation, social change, family values, intergenerational relations, cultural identity.